Operational Audit of Production Process in Reducing Defect Levels on Chemical Industries - Handoko, Bambang Leo; Setyana, Julien (International Journal of Psychosocial Rehabilitation, 2020)
increasingly fierce business competition tips, it is no exception happening also in the chemical industry. Product defects become serious problems, because they harm the company, product defects are sold at low prices and can result in lowering the company’s brand image while reducing customer satisfaction. Through this research we try to present how the operational audit process can reduce defects in production. Our research is a qualitative study; the majority of the data we collect is primary data that we obtain by observing and interviewing relevant parties. We also use secondary data in the form of literature review. Our results suggest that there are still some weaknesses in the production system in the chemical industry. Departing from these weaknesses, we provide recommendations for improvement